Pengaruh Media Televisi Terhadap Perilaku Sosial Siswa di SD Islam Terpadu Syahiral Ilmi - Izzatul Mardiah; Budi Santosa; Charles Charles (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2021)
This research is motivated by social behavior caused by one of them is television. This research is a quantitative approach that is correlational. By using a simple linear regression method. The population of students from class V Safa, V Marwa and V Thursina and samples taken using a purposive sampling technique that was recommended by the vice-principal and homeroom teacher totaling 42 students. Data obtained using a Likert scale that has been proven valid, and then processed using the SPSS 22.0 application. Based on the results of a simple regression test results obtained Fcount 5.621 <Ftable 4.08 that H0 is accepted while Ha is rejected, meaning there is an influence between television media and social behavior of students at SD IT Syahiral Ilmi. From the results of the regression equation, interpretation is obtained, meaning that if the television media is 0 or normal, then the positive social behavior of students is 169,600. Interpersonal communication variable regression interpretation of -635 means that if the television media has increased, the social behavior of students is -635. The magnitude of the influence of television media with social behavior of 12.3% and 88.7% is influenced by other factors.